Linguistic Ethnography of a Multilingual Call Center London Calling - Woydack, Johanna; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
'This book provides a fresh and insightful exploration into how call centre agents develop and use language at work. The researcher was able to do this because of her unique position within this workplace: she being one of the agents herself. This allowed her to provide a deep ethnographic account of how agents are recruited, trained and managed in this call centre, where many previous studies have relied on less knowledge and understanding of the actual and nuanced work situation.' -Jane Lockwood, The Hong Kong Polytechnic University This book presents an innovative institutional transpositional ethnography that examines the textual trajectory of "the life of a calling script" from production by corporate management and clients to recontextualization by middle management and finally to application by agents in phone interactions. Drawing on an extensive original research it provides a behind-the-scenes view of a multilingual call center in London and critiques the archetypal modern workplace practices including extensive use of monitoring and standardization and use of low-skilled precariat labor. In doing so, it offers fresh perspectives on contemporary debates about resistance, agency, and compliance in globalized workplaces. This study will provide a valuable resource to students and scholars of management studies, communication, sociolinguistics, and linguistic anthropology. Johanna Woydack is Assistant Professor at Vienna University of Business and Economics, Austria.
Chapter 1: Introduction -- Chapter 2: Getting to know Callcentral: a first encounter -- Chapter 3: The first stage of the script's career: production of "the master script" -- Chapter 4: The second stage in the script's career: adaptation of the master script -- Chapter 5: The final stage of the script's career: enactment and use of the master script -- Chapter 6: Standardization and agency intertwined.
Keywords: Linguistics -- Methodology; Ethnology; Anthropological linguistics; Multilingualism; Sociolinguistics; Industrial sociology; Research Methods in Language and Linguistics; Ethnography; Linguistic Anthropology; Multilingualism; Sociolinguistics; Sociology of Work